Cover. Issue 4 (7th August 2018) - Caulfield, Thomas R.; Richter, John E.; Brown, Emily E.; Mohammad, Ahmed N.; Judge, Daniel P.; Atwal, Paldeep S.
Abstract : The cover image, by Thomas R. Caulfield et al., is based on the Clinical Protein molecular modeling techniques investigating novel TAB2 variant R347X causing cardiomyopathy and congenital heart defects in multigenerational family, DOI:10.1002/mgg3.401 .